Diagnostic hysteroscopy versus diagnostic curettage for evaluation of endometrial pathology in patients with abnormal uterine bleeding - Al Adami, Maad S.; Al Taie, Ilham D. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: To compare the diagnostic value of hysteroscopy with conventional curettage and to evaluate the sensitivity of both methods to detect intrauterine endometrial pathology in patients with abnormal uterine bleeding.patients and Methods: This prospective study carried on 100 patients underwent diagnostic hysteroscopy as well as dilatation and curettage for abnormal uterine bleeding in two teachinghospitals, Al Yarmouk and Al Kadhmiya Teaching hospital / Baghdad from the period of Jan. 2002 to Dec. 2003, endometrial specimens were sent for separate histological study, the sensitivity of both methods were assessed according to the operative and histological findings.Results: High sensitivity and positive predictive values of hysteroscopy and directed taken biopsy for almost all pathological causes of uterine bleeding except for atrophic endometrium (66.7%) and hyperplasia (33.1%). The sensitivity of dilatation and curettage is very low compared with hysteroscopy.Conclusion: Hysteroscopy was more sensitive than dilatation and curettage in detecting endometrial polyp, submucuse fibroid, carcinoma but less sensitive than dilatation and curettage in detecting endometrial hyperplasia and atrophic endometrial . Hysteroscopy with directed biopsy taken provided high sensitivity in detecting pathological state of the endometrium.